Ischemia modified albumin in patients with obstructive sleep apnea syndrome - Seyhan, Ekrem Cengiz; Düger, Mustafa; Bolatkale, Mustafa; Eğri Kansu, Zeynep; Aynacı, Engin (European Respiratory Society Journals Ltd, 2018)
[Abstract Not Available]
28th International Congress of the European-Respiratory-Society (ERS) -- SEP 15-19, 2018 -- Paris, FRANCE
WOS: 000455567105488
Keywords: Obstructive Sleep Apnea; Syndrome; Ischemia Modified